Peran Masyarakat Terhadap Tempat Olah Sampah Setempat (TOSS) di Desa Paksebali - Putu Eka Febyanti; A.A. Ayu Murniasih; I Nyoman Suarsana (Department of Anthropology Udayana University, 2021)
The community is the main key to the waste problem. The role of the community in waste management in addition to having an impact on the sustainability of the Tempat Olah Sampah Setempat (TOSS) also greatly affects the personal condition of each. Most of the waste comes from household waste. No matter how great the program made by the government to tackle waste will be useless if in the community there is a lack of awareness of the environment. This study was researched because Paksebali Village is one of the villages that has won Adi Pura which is considered capable of providing future examples of the importance of the role of the community in waste management. The discussion focused on the role of the Paksebali Village community in managing their waste and also the implications for the community.